Cyclosporine nephrotoxicity - Busauschina, Aigerim; Schnülle, Peter; Woude, Fokko J. van der (Transplantation proceedings, 2004)
Cyclosporine (CsA) is the current primary immunosuppressant for the prevention of allograft rejection in solid organ transplantation. However, owing to its molecular mechanism of action the drug is associated with various adverse side effects (eg, nephrotoxicity). Histological changes appear as obliterative vasculopathy of the afferent arteriole and tubulointerstitial fibrosis in advanced cases. The underlying pathomechanisms of this condition reflect an altered release of vasoactive substances, such as angiotensin II, endothelin, prostaglandins, and nitric oxide as well as the stimulation of proliferative genes such as transforming growth factor-beta, osteopontin, and collagen I and IV. Potential strategies for the prevention of nephrotoxicity are discussed.